Aplicabilidade da justiça restaurativa no Direito Penal Brasileiro - Hueso, Cauê Costa (2015)
The topic of this paper is the applicability, function and execution of restoring justice, as an alternative to imprisonment. Often, the minimum penal law is not considered regarding strongly sanctioned penal law, supported by society, which does not see any more solutions to the growing criminality, and thus accepts any quick and strong response, even if in practice it brings just an illusion of safety. Indeed, the maximum penal law does not show reduction of criminality, and the application of the rule is getting more and more trivial, with discredit in its function of general prevention, concerning so many criminal kinds, high penalties, and so much impunity. In many situations, a mere apology brings more benefits to the ones involved, and avoids that the whole judicial apparatus is moved. The restoring justice will be analyzed as an alternative to the sanctions imposed, bringing a smaller recidivism when applied, and consequently, a more adequate and proved resocialization